2019
DOI: 10.1021/acschembio.8b00972
|View full text |Cite
|
Sign up to set email alerts
|

Crystal Structures of Fumarate Hydratases from Leishmania major in a Complex with Inhibitor 2-Thiomalate

Abstract: Leishmaniases affect the poorest people on earth and have no effective drug therapy. Here, we present the crystal structure of the mitochondrial isoform of class I fumarate hydratase (FH) from Leishmania major and compare it to the previously determined cytosolic Leishmania major isoform. We further describe the mechanism of action of the first class-specific FH inhibitor, 2-thiomalate, through X-ray crystallography and inhibition assays. Our crystal structures of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 32 publications
0
8
0
Order By: Relevance
“…Recently, we determined the crystal structures of mitochondrial and cytosolic isoforms of class I FHs in L. major , a parasite responsible for the neglected tropical disease leishmaniasis. 5 , 14 These structures revealed that mitochondrial LmFH-1 and cytosolic LmFH-2 have very similar homodimeric structures with each monomer composed of two domains, an N-terminal domain and a C-terminal domain, arranged around the catalytic [4Fe-4S] cluster. 5 , 14 A co-crystal structure of LmFH-2 revealed substrate S -malate bound to the unique iron of the [4Fe-4S] cluster as well as conserved active site residues that play a key role in catalysis.…”
Section: Discussionmentioning
confidence: 94%
See 3 more Smart Citations
“…Recently, we determined the crystal structures of mitochondrial and cytosolic isoforms of class I FHs in L. major , a parasite responsible for the neglected tropical disease leishmaniasis. 5 , 14 These structures revealed that mitochondrial LmFH-1 and cytosolic LmFH-2 have very similar homodimeric structures with each monomer composed of two domains, an N-terminal domain and a C-terminal domain, arranged around the catalytic [4Fe-4S] cluster. 5 , 14 A co-crystal structure of LmFH-2 revealed substrate S -malate bound to the unique iron of the [4Fe-4S] cluster as well as conserved active site residues that play a key role in catalysis.…”
Section: Discussionmentioning
confidence: 94%
“… 5 , 14 These structures revealed that mitochondrial LmFH-1 and cytosolic LmFH-2 have very similar homodimeric structures with each monomer composed of two domains, an N-terminal domain and a C-terminal domain, arranged around the catalytic [4Fe-4S] cluster. 5 , 14 A co-crystal structure of LmFH-2 revealed substrate S -malate bound to the unique iron of the [4Fe-4S] cluster as well as conserved active site residues that play a key role in catalysis. 5 In this study, we present mutagenesis, biochemical, and structural characterization of LmFH-2 and propose a catalytic mechanism for class I FHs.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…109 6MSO catalyzes the stereospecific reversible conversion of fumarate to S-malate. This reaction is part of the tricarboxylic acid (TCA) cycle, takes part of the succinic fermentation pathway, participates in DNA repair processes and is proposed to provide fumarate for the de novo pyrimidine biosynthetic pathway 110. Finally, aldolase L. Peptidyl-prolyl cis-trans isomerase (PDB ID: 4S1E) accelerates the folding process of proteins.…”
mentioning
confidence: 99%